Exploring the interplay between diet, obesity, mental health, and the gut microbiota: the MIND-GUT intervention study, study protocol - Gustafson, Deborah; Rothenberg, Elisabet; Steingrimsson, Steinn; Carlsen, Hanne Krage; Belloni, Fabrizio; Eruvuri, Nagalakshmi; Knez, Rajna; Olsson, Erika; Burk, Robert D.; Cena, Hellas; De Giuseppe, Rachele; Tognon, Gianluca (Frontiers in Nutrition, 2025)
BackgroundObesity and mental health disorders often co-occur, contributing to individual suffering and healthcare costs. Diet plays a key role in both weight management and mental wellbeing and may influence these through its impact on the gut microbiota. However, the mechanisms linking diet, obesity, and mental health remain insufficiently understood.AimWe propose to conduct the MIND-GUT study in Sweden to evaluate feasibility as primary outcome (retention, adherence, and acceptability) of a 12-week dietary intervention based on the MIND diet and, as secondary outcomes, the influence of the latter on weight loss and mental wellbeing in adults with overweight and obesity [body mass index (BMI) ≥30 kg/m2]. The study will also explore changes in gut microbiota composition and diversity.MethodsIn this randomized trial, 126 adults with obesity will be assigned to either an intervention group following a MIND diet or a control group receiving general dietary advice. Energy intake targets will be <2,300 kcal/day for men and <1,900 kcal/day for women. The primary outcomes are retention, adherence, and intervention acceptability (the latter assessed through qualitative interviews). Secondary outcomes include changes in body weight, BMI, waist and hip circumferences, fat mass, and mental health including perceived stress, depression, and anxiety symptoms. Gut microbiota diversity and composition will be analyzed from stool samples collected at baseline and 12-week follow-up.DiscussionThis study will offer valuable insights into the relationship between diet, mental health, obesity, and the gut microbiota. Results will inform the design of future large-scale trials assessing the MIND diet's potential as a strategy for improving physical and mental health.